Factors Affecting the Value-Relevance of Capitalized Exploration and Evaluation Expenditures Under IFRS 6. (October 2021) - Ferguson, Andrew; Kean, Stephen; Pündrich, Gabriel
This study examines factors affecting the value-relevance of financial and nonfinancial disclosure in the context of the long contentious International Financial Reporting Standard 6 (IFRS 6). Relative to the capitalization of R&D expenditures, IFRS 6 follows a far less restrictive approach, delaying the requirement for probable future economic benefits in settings of high uncertainty. We compare the value-relevance of this asset with that of nonfinancial information commonly reported by mining firms, namely mineral resource estimates. We report evidence that investors utilize nonfinancial information to assess the value-relevance of financial information, initially focusing on whichever information is timelier. We do not find evidence that investors prefer conservative reporting practices in a setting with high uncertainty; rather we provide evidence that investors interpret the capitalization decision as a signal of project viability. This finding is of particular relevance to the ongoing Intangible Assets project being conducted by the International Accounting Standards Board (IASB). JEL classifications: G12, G14